Critical wood-particle properties in the production of particleboard. Issue 5 (3rd September 2022) - Niemz, Peter; Sandberg, Dick
ABSTRACT: Particleboard is an important base-material in furniture and building applications and its annual production capacity worldwide is over 100 million m 3 . Wood is the main raw material used, although the feasibility of non-wood alternatives exists. This technical note summarises information about how wood-particle geometry affects the bulk density and mat density, two important parameters in the particleboard production.